Husbandry, nutrition and productivity of goats and sheep in tropical Africa - Wilson, R.T. (1982)
Sheep and goats of tropical Africa were studied. Data on breed types, management systems, ownership, nutrition and productivity included for both species. Their contributions to live weight biomass, meat production, and registered slaughtering units described. Some measured production parameters for African goats and sheep in semi-arid areas included with potential suggestions for improved production.